2006
DOI: 10.1080/13550280600957414
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant antibodies generated from both clonal and less abundant plasma cell immunoglobulin G sequences in subacute sclerosing panencephalitis brain are directed against measles virus

Abstract: Increased immunoglobulin G (IgG) and intrathecally produced oligoclonal bands (OGBs) are characteristic of a limited number of inflammatory central nervous system (CNS) diseases and are often directed against the cause of disease. In subacute sclerosing panencephalitis (SSPE), the cause of disease and the target of the oligoclonal response is measles virus (MV). The authors previously showed that clonally expanded populations of CD38+ plasma cells in SSPE brain, the likely source of OGBs, are directed against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…As described above, oligoclonal IgG antibody bands, with measles virus-restricted specificities, are characteristically found in the serum and CSF of patients with SSPE (Mehta et al, 1994; Burgoon et al, 2006; Tschen et al, 2006). These oligoclonal bands are a hyperimune response to measles virus antigens, which, despite their neutralizing activity, are unable to control the viral infection (Mehta et al, 1994).…”
Section: Measles Virusmentioning
confidence: 73%
“…As described above, oligoclonal IgG antibody bands, with measles virus-restricted specificities, are characteristically found in the serum and CSF of patients with SSPE (Mehta et al, 1994; Burgoon et al, 2006; Tschen et al, 2006). These oligoclonal bands are a hyperimune response to measles virus antigens, which, despite their neutralizing activity, are unable to control the viral infection (Mehta et al, 1994).…”
Section: Measles Virusmentioning
confidence: 73%
“…Having demonstrated that the array was able to detect anti-lipid antibody profiles in MS and control CSF, we next investigated 100 IgG1 recombinant antibodies (rAb) derived from clonally expanded CSF B cells/plasma blasts (Owens et al, 2009) obtained from patients with MS (n = 11; 73 rAb) and other CNS inflammatory diseases (ONID; n = 6; 27 rAb) (Table 2) (Owens et al, 2006a,b; Burgoon et al, 1999, 2006; Bennett et al, 2009). It is known that CSF-resident B cells may produce OCBs (Obermeier et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, oligoclonal bands indicative of restrictive IgG synthesis within the blood-brain barrier have been detected in the CSF of VE cases [4]. The presence of chronic CSF pleocytosis, together with the restriction of CSF IgG production indicative of a specific antigen-driven immune response [5], support a persistent CNS infection as the cause of VE.…”
Section: Laboratory Findingsmentioning
confidence: 98%